2022
DOI: 10.1002/smi.3147
|View full text |Cite
|
Sign up to set email alerts
|

The psychological response and perception of stress during the COVID‐19 pandemic in Slovenia: Three‐wave repeated cross‐sectional study

Abstract: In addition to COVID‐19 being a health threat, its longevity and restrictions act as significant stressors and risk for mental health. In the current study, we take a look at how psychological response, both its positive aspects, for example, mental well‐being and life satisfaction, and its negative aspects, for example, anxiety and COVID‐19 anxiety, have changed as the pandemic has continued (first three waves in Slovenia). Additionally, we are interested in whether the psychological response is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
2
4
0
15
Order By: Relevance
“…Both surveys showed the lowest ratings related to illness coherence, reflecting the ability to make sense of and cope with the pandemic. These findings suggest that mental representation of COVID-19 changed in some ways, and what is common to our results and those reported by others is the increase in knowledge about COVID-19, stronger sense of negative emotions and consequences of COVID-19 after several waves of the pandemic [4,31,[33][34][35][36]39]. Our findings are consistent with results reported in a longitudinal study [24], which showed that the highest level in the hierarchy of COVID-19 representations was occupied by a sense of negative consequences, while the lowest level was occupied by sense of personal control.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both surveys showed the lowest ratings related to illness coherence, reflecting the ability to make sense of and cope with the pandemic. These findings suggest that mental representation of COVID-19 changed in some ways, and what is common to our results and those reported by others is the increase in knowledge about COVID-19, stronger sense of negative emotions and consequences of COVID-19 after several waves of the pandemic [4,31,[33][34][35][36]39]. Our findings are consistent with results reported in a longitudinal study [24], which showed that the highest level in the hierarchy of COVID-19 representations was occupied by a sense of negative consequences, while the lowest level was occupied by sense of personal control.…”
Section: Discussionsupporting
confidence: 90%
“…There was also a change in the emotional representation of the disease. Initial increase in negative emotions [23,31] was followed with a slight decrease in the negative perceptions of COVID-19 [4], and even with a sense of positive changes in life [32]. However, a meta-analysis [33] of research reports focusing on mental health during the COVID-19 pandemic showed that stress and mental burden in this case were comparable to war time experiences.…”
mentioning
confidence: 94%
“…For example, the longitudinal investigation conducted by Benke et al (2022) suggested that participants’ life satisfaction decreased from baseline (May 2020) to 6 months (November 2020) and 1-year follow-up (June 2021). Similar effects were reported by Kozina et al (2022) in their related 3-wave longitudinal research. These parallel findings suggested a similar pattern of decrease in life satisfaction since the beginning of this worldwide health crisis.…”
Section: Introductionsupporting
confidence: 88%
“…Moreover, a three-wave panel survey of the population in Denmark showed a significant decrease in psychological well-being from April 2020 to December 2020 ( Sønderskov et al., 2021 ) and a recent study identified the fear of contracting the virus as a strong risk factor in developing stress-related conditions during the COVID-19 pandemic ( Hagger et al., 2020 ). Finally, a three-wave longitudinal study resulting in the three lockdowns in Slovenia showed a decrease in psychological well-being and an increase in COVID-19 related anxiety from wave 1 to wave 3 especially for those individuals who perceived wave 2 and wave 3 as more stressful than wave 1 ( Kozina et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies longitudinally explored the population's mental health on successive time points from the beginning of the pandemic (e.g., Kozina et al., 2022 ; Sønderskov et al., 2021 ). However, the vast majority of these studies focused on specific psychiatric symptoms (e.g., anxiety) or included samples with pre-existing mental health problems.…”
Section: Introductionmentioning
confidence: 99%